AN ANALYSIS OF STUDENTS’ SPEAKING DIFFICULTIES IN ROLE PLAY ACTIVITIES - Elsa Silvana Destriani; Wahid Hasim (Institut Pendidikan Indonesia Garut, 2019)
This research was aimed to find the students’ difficulties in speaking English and to find the factors contributing to students’ difficulties in speaking English. The research used qualitative method for the answer the problem statement. The sample of this study was all students of eleventh grade of a senior high school in Garut which used population sampling technique. Based on the data from the result of this research showed that: 92% of the students’ difficulties in speaking, 80% of students had limited vocabulary, 70% pronunciation, 20% nervousness. Factors contributing to students’ difficulties in speaking were that 100% students preferred to speak in their mother tongue (Sundanese) rather than English, they are lazy to read and learned new words, 92, 6% the students did not had motivation and the teachers’ teaching style was also one of the factors contributing to students’ difficulties in speaking English.